Rubber-modified polybenzoxazine-based materials for surface coating applications - Caldona, Eugene B. (College of Engineering, University of the Philippines Diliman, 2014)
This study demonstrates the preparation of rubber-modified polybenzoxazine (PBZ) in which different additives such as graphene oxide (GO), polyaniline (PANI), and nano-silica (SiO2) are added separately and the resulting materials are used as surface coatings. Given the fact that PBZ is known for its near-zero shrinkage upon polymerization, chemical resistance, and good dielectric, thermal, and mechanical properties, PBZ has low surface free energy and low water absorption making it an excellent polymer candidate for protective coating study. GO is added because of its ability to form a tortuous path for the corrosive medium leading to reduced permeability and enhanced barrier property. On the other hand, the presence of PANI, a conducting polymer, promotes passivation by forming a thin layer of metal oxides that further increase the anodic protection of the coating. Lastly, on top of providing superior corrosion protection, the addition of nano-SiO2 introduces surface roughness that results to excellent anti-wettability, anti-icing, self-cleaning property, and superoleophilicity. Combined with good thermal and adhesion properties, the rubber-modified PBZ with different additives are said to be very promising surface coating materials for a variety of protection application purposes.